Tolerance levels of Tilapia Mossambica to Excoecaria Agallocha Aqueous extract - Jimenea, Remo (1989)
a 24-hour short-term static bioassay on the toxicity of Ecoecaria agallocha aqueous extract was determined by exposing almost uniform sizes of Tilapia mossambica to the varying concentrations of the toxicants such as 0.5, 1.0, 1.8, 3.2, 4.2, 6.0, 9.0 and 18.0 expressed in parts per thousand (ppt.), and pond snails to test concentrations such as 5.0, 10.0, 15.0, 20.0, and 40.0 ppt. Each concentration, using aquaria as experimental units, was replicated three times. Throughout the duration of the experiment aeration was provided. It has been observed that the length of time needed to effect total mortality in fish and pond snails becomes shorter with increasing concentrations of Excoecaria agallocha aqueous extract. For tilapia, it was noted that at the concentrations of 18 ppt., a 4-hour time was needed to completely kill the fish. By the 10th hour, all fishes at concentrations of 9 ppt. died, while longer periods were needed for all the other test concentrations. Similar trend of mortality was observed for pond snails. At highest concentration (40ppt.) total kill was observed at the first hour of the experiment. For 20 ppt., it required two hours to kill all the snails; 3 hours for 10 and 15 ppt.; and 5 hours for 5 ppt. No attempt was made to determine the biodegradability of Alipata extract. However,observations made that even on the 5th day, Alipata extract could still effect death to Tilapia mossambica and pond snails. In fact, it became more effective as evidenced by the shorter time the fish met their death, when introduced to the differentconcentrations. No explanation could yet be made as to why such occurrence. Test fish upon exposure to varying concentrations of Alipata extract exhibited loss of equilibrium as manifested by erratic movements and occasional gasping of oxygen at the water surface.
Special Problem (Master of Education (Chemistry). -- [Iloilo City] : UPV-CAS, October 1989.